New Zealand English. - Bell, Allan, 1947-; Kuiper, Koenraad (Varieties of English Around the World., 2000)
New Zealand English is currently one of the most researched varieties of English world-wide. This book presents an up-to-date account of all the major aspects of New Zealand English by leading scholars as well as younger specialists in each of the major fields of enquiry. The book is authoritative in its range and represents not only a synopsis of past research, but also new research in many areas of study. It is of interest not just to specialists in regional varieties of English but many of the chapters detail new approaches to the study of dialect phenomena. It contains an introduction describing the external history of New Zealand English and the development of the study of New Zealand English. It comes with a full bibliography of work on New Zealand English and is fully indexed. This book is a significant landmark in the study of English varieties and will prove indispensable for anyone who is a student of English and New Zealand English.